Nanobiotechnology - Balaji, Subbiah (Chennai : MJP, 2010)
Nanobiotechnology: An Overview Biomaterials Science Fabrication and Characterization of Nanostructures Nanotechnology in Biomedical Applications Nanomedicine and Novel Drug Delivery Systems Health and Environmental Impacts of Nanotechnology
Includes bibliographical references and Index 223-227p.
Keywords: Nanobiotechnology; Physics; Nano science